Effect of Heat Treatment and Types of Bacteria on Corrosion Resistance At Steel Materials (API 5L and ASTM A53) in the Marine Environment - Herman Pratikno; Harmin Sulistyaning Titah; Febrian Ramadhana Sastradimaja (Department of Ocean Engineering, 2017)
Corrosion is the result of damage to material degradation through a chemical or electrochemical reaction spontaneously and causes a decrease in the quality of the material. One of the causes of corrosion is the presence of bacteria on the material. The danger posed by corrosion is fatality, especially on offshore platforms, namely cessation of production at offshore rigs. This study is an experiment using material carbon steel API 5L Grade B and ASTM A53 commonly used as a base for the manufacture of subsea pipelines. Material to be heat-treated before immersion for corrosion test in artificial seawater (salinity 35‰), which have been added with bacteria and without bacteria. The method used in measuring the rate of corrosion steel data is the weight loss. The highest corrosion rate of the original material ASTM A53 and API 5L with the addition of T. ferrooxidans bacteria are, respectively, 3.63 mpy and 3.50 mpy. While the lowest corrosion rate of ASTM A53 and API 5L both with heat treatment but without adding bacteria are 2.33 mpy and 2.01 mpy. This indicates that the steel API 5L have high levels of corrosion resistance, better than ASTM A53 in the marine environment with bacteria or without bacteria.